2014
DOI: 10.1111/ics.12150
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a human epidermis model reconstructed from hair follicle keratinocytes and comparison with two commercially models and native skin

Abstract: ORS cell-based reconstructed epidermis is a valid and reproducible model for human epidermis and it may be used to evaluate the effects of active substances and cosmetic formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 25 publications
(56 reference statements)
1
37
0
Order By: Relevance
“…After 14 days culture at the air/liquid interface, the RHE model presented a similar morphology and three-dimensional architecture to those of native epidermis with the presence of the classical four skin layers (stratum basale, stratum spinosum, stratum granulosum and the outermost layer stratum corneum). The RHE model reconstruction was reproducible and the expression of proliferation and differentiation markers was close to the marketed epidermal substitutes and skin [16]. Moreover, the hair follicle-derived RHE is a convenient and easy-to-handle in vitro RHE model and a more reliable source of biological material than skin explants.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…After 14 days culture at the air/liquid interface, the RHE model presented a similar morphology and three-dimensional architecture to those of native epidermis with the presence of the classical four skin layers (stratum basale, stratum spinosum, stratum granulosum and the outermost layer stratum corneum). The RHE model reconstruction was reproducible and the expression of proliferation and differentiation markers was close to the marketed epidermal substitutes and skin [16]. Moreover, the hair follicle-derived RHE is a convenient and easy-to-handle in vitro RHE model and a more reliable source of biological material than skin explants.…”
Section: Introductionmentioning
confidence: 70%
“…Tissue engineering was performed in-house according to the recently published protocol [16]. The 1.12 cm 2 epidermal equivalent consisted of airlifted, living, multilayered, normal human keratinocytes cultured for 16 days on an inert polycarbonate filter.…”
Section: Preparation Of Reconstituted Human Epidermis and Skin Explantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, very recently Bacqueville et al (2017) reported that COMT mRNA was strongly expressed in their ORS-RHE model (Guiraud et al 2014). …”
Section: Xenobiotica-metabolizing Enzymes In the Human Skin Includingmentioning
confidence: 66%
“…Another possibility is to seed the keratinocytes onto a de‐epidermised dermis derived from normal skin . A further option is to use keratinocytes derived from the outer root sheath of hair follicles to prepare skin models . This provides a non‐invasive way to generate skin models with keratinocytes derived from patients.…”
Section: D Skin Modelsmentioning
confidence: 99%